Digital Marketing-Based Tourism Destination Rebranding Strategy: A Case Study of Marine Tourism Development in Gorontalo - Rahayu Agustina Ishak; Dedy Suryadi; Aulia Abdul Rahman (CV Edujavare Publishing, 2026)
This study aims to analyze digital marketing-based destination rebranding strategies with a case study on marine tourism development in Gorontalo. The research method used is descriptive qualitative based on a literature review by examining various scientific sources related to rebranding, digital marketing, and sustainable tourism. The results of the study show that the application of digital marketing strategies can enhance the image of a destination through interactive promotion, strengthening of local identity, and participation of coastal communities. Rebranding not only covers visual and promotional aspects, but also the transformation of cultural values ​​and environmental sustainability. A collaborative approach between the government, the community, and business actors is a key factor in the successful development of competitive and globally competitive marine tourism in Gorontalo.